Лавинні процеси в Українських Карпатах = Avalanche process in Ukrainian Carpathians - Bilanyuk, Volodymyr; Tikhanovich, Ievhen (Journal of Education, Health and Sport, 2015)
Bilanyuk Volodymyr, Tikhanovich Ievhen. Лавинні процеси в Українських Карпатах = Avalanche process in Ukrainian Carpathians. Journal of Education, Health and Sport. 2015;5(7):96-104. ISSN 2391-8306. DOI 10.5281/zenodo.19307 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A96-104 https://pbn.nauka.gov.pl/works/578565 http://dx.doi.org/10.5281/zenodo.19307 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015. Лавинні процеси в Українських Карпатах Avalanche process in Ukrainian Carpathians Volodymyr Bilanyuk, Ievhen Tikhanovich Володимир Біланюк – кандидат географічних наук, доцент, декан географічного факультету Львівського національного університету імені Івана Франка. Євген Тиханович – старший лаборант Розтоцького ландшафтно-геофізичного стаціонару Львівського національного університету імені Івана Франка. Volodymyr Bilanyuk – candidate of geographical sciences, dean of the Faculty of Geography, Ivan Franko National University of Lviv. Ievhen Tikhanovich – senior laboratory assistant of Roztochchya landscape-geophysical scientific full-time department, Ivan Franko National University of Lviv. Ключові слова: лавина, сніг, Українські Карпати, сніголавинна станція, лавинні дослідження. Keywords: avalanche, snow, Ukrainian Carpathians, snow-avalanche station, avalanche research. Анотація. У статті досліджено особливості лавинних процесів в Українських Карпатах. Охарактеризовано історію дослідження лавин і лавинних територій цієї гірської структури. Наведено основні завдання для дослідження лавинної активності. Висвітлено особливості сучасних досліджень лавинних процесів та описано діяльність українських сніголавинних станцій. Проаналізовано головні типи лавин, які характерні для досліджуваної територій. Описано лавинну активність території за різні часові періоди. Проаналізовано територіальне поширення лавин в Українських Карпатах, визначено умови їх сходження. На орогідрографічних схемах проілюстровано місця сходження лавин на досліджуваних територіях. Abstract. In the articles are research peculiarities of avalanche process in Ukrainian Carpathians. The history of the avalanches and avalanche areas study of this mountain structure are characterized. Main basic avalanche activity research tasks are give an example. Depicted the peculiarities of avalanche processes current research and described the function of Ukrainian snow-avalanche stations. The main types of the avalanche, that are typical for research territory are analyzing. Depicted avalanche activity in Ukrainian Carpathians for the different time period. Analyzes territorial distribution of avalanches in the Ukrainian Carpathians and described the condition of their sliding. The avalanche slide pleases on research territory are illustration on orogidrographical model.